Physiological and Neurobehavioral Disturbances Induced by Al2O3 Nanoparticle Intoxication in Nile Tilapia Fish: Benefits of Dietary Chamomile Essential Oil - Mayada R. Farag; Chuntian Zheng; Heba S. A. Gharib; Enas EL-Hady; Eman A. A. Mahdy; Azza M. A. Abo-Elmaaty; Shimaa M. Abou-Zeid; Mahmoud Alagawany; Alessandro Di Cerbo; Mahmoud M. Azzam; Abdulaziz A. Al-Abdullatif; Mona A. Hassan (Aquaculture Nutrition)
Despite the usage of nanoparticles (NPs) is rapidly increasing, several experts have noted the risk of their release into ecosystems and their potential negative impacts on biological systems. However, the available studies on the neurobehavioral impacts of aluminum oxide nanoparticles (Al2O3NPs) on aquatic organisms are little. Hence, this study targeted to ascertain the harmful effects of Al2O3NPs on behavioral characteristics and genotoxic and oxidative damages in Nile tilapia fish. In addition, the beneficial role of chamomile essential oil (CEO) supplementation in reducing these effects was also investigated. In the current study, fish were distributed into 4 equal groups (n=60 fish per group). The control group was fed a plain diet only, the CEO group received a basic diet complemented with CEO at a level of 2 mg/kg diet, the ALNP group received a basic diet and was exposed to an approximate concentration of 1/10th LC50 of ALNPs nearly 5.08 mg/L, and the combination group (ALNPs/CEO group) received a basal diet coadministered with ALNPs and CEO at the aforementioned percentages. The findings revealed that O. niloticus exhibit neurobehavioral changes along with changes in the level of GABA, monoamines in the brain tissue, and serum amino acid neurotransmitters, besides a reduction of AChE and Na+/K+-ATPase activities. In addition to brain tissue oxidative damage with upregulation of proinflammatory and stress genes, such as HSP70 and caspase-3, supplementation of CEO significantly reduced the negative impacts of ALNPs. These results showed that CEO has neuroprotective, antioxidant, genoprotective, anti-inflammatory, and antiapoptotic properties in fish that have been exposed to ALNPs. Therefore, we advise its usage as a valuable addition to fish diet.